Postglacial history of East European boreal forests in the mid‐Kama region, pre‐Urals, Russia. (24th April 2020) - Shumilovskikh, Lyudmila S.; Schmidt, Monika; Pereskokov, Mikhail; Sannikov, Pavel
Abstract : The Ural Mountains are an important climatic and biogeographical barrier between European and Siberian forests. In order to shed light on the postglacial formation and evolution of the boreal forests in the European pre‐Urals, we obtained a peat sediment core, Chernaya, from the Paltinskoe bog located between the southern taiga and hemiboreal forest zone in the mid‐Kama region. We carried out pollen analysis, non‐pollen palynomorph analysis, loss‐on‐ignition tests and radiocarbon dating. Radiocarbon dated records provide centennial to decennial resolution of the vegetation and environmental history of the European pre‐Urals for the last 8.8 ka. The postglacial formation of the pre‐Uralian hemiboreal forests reveals four important phases: (i) the dominance of Siberian taiga and forest‐steppe in the Early Holocene and beginning of the Middle Holocene (8.8–6.9 ka), indicating a dry climate; (ii) the spread of spruce and European broadleaved trees in the Middle Holocene (6.9–4 ka) under wetter climate conditions; (iii) the maximum extent of broadleaved trees coinciding with the arrival and spread of Siberian fir in the Late Holocene (4–2.3 ka); and (iv) the decline of broadleaved trees since the Early Iron Age (2.3 ka – present) possibly due to general climate cooling and logging. While temperate broadleaved trees possibly spread from local refugia in the Urals, fir arrived from Siberia and spread further west. The carbon accumulation rate of Paltinskoe bog (18.9±10.16 g C m −2 a −1 ) is close to the average value of carbon accumulation of northern peatlands. Local development of peat is characterized by non‐gradual growth with a phase of intensive carbon accumulation between 3.5 and 2.3 ka. The vegetation was strongly influenced by fire in the Early Holocene and by humans since the Early Iron Age practicing deforestation, agriculture and pasture. Phases of increased anthropogenic activity correlate well with the local archaeological data.